A few dominant bacteria and their genomic basis in mediating distinct ecosystem functions. (30th June 2021) - Ren, Minglei; Wang, Jianjun
Summary: Species attributes such as abundance and traits are important determinant components for ecosystem functions (EFs), while their influences on distinct functions remain understudied. Here, we linked 753 treehole bacterial communities to two distinct types of EFs, including the three broad functions of respiration, metabolic activity and cell yield and the four narrow functions related to specific organic matter degradation. Towards high occurrence of phylotypes or traits, the dependency of broad EFs on species abundance or traits increased, whereas the dependency of narrow functions decreased. Among the immense number of bacterial phylotypes, the relative abundance of only 5.05% of phylotypes (that is, 542 phylotypes), but accounting for 68.60% of total abundance, were significantly related to both distinct EFs ranging from 2 to 7 functions, the level of which was used to quantify species functional generality. Such 'low species number, high relative abundance and strong functional generality' features for these 542 phylotypes could be further potentially linked to their enriched functional genes involved in cellular processes including nutrient acquisition, environmental adaptation and cell growth. Our study highlights the key role of a handful of microbial species in determining and anticipating distinct EFs by explicitly considering their abundance and trait attributes.